SEROPREVALENCIA DE ARTRITIS ENCEFALITIS VIRAL CAPRINA EN EL NOROESTE DE LA PROVINCIA DE YAUYOS, LIMA - Callapiña E., Eric (2002)
A study of seroprevalence of caprine arthritis encephalitis virus (CAEV) in a native goat population of an extensive system in the northwest of Yauyos, Lima (Peru) was carried out. Serum samples (n = 533) were collected from adult male and female goats for detection of antibodies against CAEV by agar gel immunodiffusion test. None of the animals were reactors to CAEV indicating that the tested animals were not exposed to the CAEV and suggested a low or absence of the infection in native goats in this area.